The Internationalization of Higher Education in Turkey: Creating an Index - Kirecci, Mehmet Akif; Bacanli, Hasan; Erisen, Yavuz; Karadag, Engin; Celikoz, Nadir; Dombayci, Mehmet Ali; Toprak, Metin; Sahin, Mehmet (TURKISH EDUCATION ASSOC, 2016)
The aim of this study is to test the validity and reliability of the Internationalization Index of Higher Education in Turkey, which provides a ranking of institutions of higher education in Turkey according to their degree of internationalization. The item discrimination, construct validity (exploratory and confirmatory factor analyses), and internal consistencies of the index's indicators and subindicators were tested using data obtained from 300 faculty members. The findings obtained showed that the index was made up of five indicators-(i) university research performance, (ii) curricular efficiency, (iii) international linkages, (iv) student support, and (v) urban sufficiency as well as of 33 subindicators, and that the index was valid and reliable. The study then made use of the Delphi method to establish the weight of the index's indicators and subindicators. In sum, it can be said that the study effectively constitutes a proof toward utilization of the Internationalization Index of Higher Education in Turkey for the ranking of institutions of higher education in terms of internationalization.
Keywords: Higher education; University; Internationalization; Index; Quality; Education & Educational Research